2022
DOI: 10.3390/ijerph191710542
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact and Influencing Factors during Different Waves of COVID-19 Pandemic on Healthcare Workers in Central Taiwan

Abstract: Background: This study aims to explore differences of psychological impact and influencing factors that affected Taiwanese healthcare workers (HCW) during the first and second wave of COVID-19. Methods: a cross sectional survey of first-line HCW during November 2021 to February 2022: 270 paper questionnaires were issued and the valid response rate was 86% (231). For statistical analysis, descriptive statistics, Pearson correlation, and multivariate linear regression were used. Results: regardless of the wave o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…In line with our study’s findings, a cross-sectional study [ 10 ] amongst Taiwanese frontline HCWs showed persistently poor MHOs (anxiety, depression and insomnia) irrespective of the wave of the pandemic. This was partly explained by the changes in workload, work schedules, working overtime and concerns over the risk of infection [ 10 , 11 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with our study’s findings, a cross-sectional study [ 10 ] amongst Taiwanese frontline HCWs showed persistently poor MHOs (anxiety, depression and insomnia) irrespective of the wave of the pandemic. This was partly explained by the changes in workload, work schedules, working overtime and concerns over the risk of infection [ 10 , 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…In line with our study’s findings, a cross-sectional study [ 10 ] amongst Taiwanese frontline HCWs showed persistently poor MHOs (anxiety, depression and insomnia) irrespective of the wave of the pandemic. This was partly explained by the changes in workload, work schedules, working overtime and concerns over the risk of infection [ 10 , 11 ]. Similarly, a Chinese study that was carried out about 3 years after the 2003 severe acute respiratory syndrome (SARS) outbreak showed persistently high levels of psychological stress, which was thought to be attributed to working in a high-risk environment and having a fear of being a source of infection to a family member(s) [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…5 Epidemiologic studies around the world have shown that about 33-50% of healthcare workers have symptoms of anxiety 6,7 and nearly 26-60% of healthcare workers have symptoms of depression. 8,9 The evidence shows that mental disorders have a significant impact on individuals and healthcare organizations. Previous studies suggest that they may cause chronic conditions, such as cardiovascular disease, and physical symptoms such as fatigue, dizziness, vomiting, the pre-survey, we determined that the prevalence of anxiety is about 30%, and so we took the p-value of 0.3, α of 0.05, δ of 0.05 and taking into account the 20% nonresponse rate, we calculated the minimum sample size as 387.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) declared the COVID-19 a pandemic in March 2020; thereafter, dramatic global spread occurred 1 . Currently, the number of infections and the case fatality rate continue to accumulate 2 , 3 . Compared to other countries, Taiwan was relatively resilient to the threat of COVID-19 due to acute awareness of the news about COVID-19 and rapid implementation of approaches to protect public health by the government 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to previous waves, the Omicron variants were more contagious 6 , 7 , with breakthrough infections occurring even in individuals with multiple vaccine combinations 8 . With the greater concern over infection during this wave, it is plausible that psychological impacts such as frustration, irritability, burnout, and insomnia would become widespread in response to the prolonged restrictions of social isolation and quarantine practices 2 . Thus, it is vital to explore the psychological impact of COVID-19 on Taiwanese individuals during this wave.…”
Section: Introductionmentioning
confidence: 99%